Building crystal structures of conjugated polymers through X‐ray diffraction and molecular modeling. (19th July 2021) - Yao, Ze‐Fan; Li, Qi‐Yi; Wu, Hao‐Tian; Ding, Yi‐Fan; Wang, Zi‐Yuan; Lu, Yang; Wang, Jie‐Yu; Pei, Jian
Abstract: Crystal structure of conjugated molecules and polymers is fundamentally critical to understand their multilevel microstructures, carrier transport, and diverse functions. However, to determine the crystal structure of conjugated polymers is a significant challenge, mainly due to the poor crystallinity, weak diffraction, and instability under high‐energy radiation. Here, we build the possible crystal structures of eight typical conjugated polymers, covering several widely used molecular segments in organic optoelectronics. We model the packing structures of these seed polymers based on synchrotron X‐ray diffractions and molecular simulations. These crystal structures provide a new platform to predict the packing structures of more related polymer systems, extending the molecular scope. Based on this polymer crystal structure database, the multiscale microstructures and charge transport properties of conjugated polymers can be predicted before experiments. This study sets up a polymer crystal structure database to eliminate the current trial‐and‐error approaches and accelerating the design of high‐performance conjugated polymers. Abstract : Combining X‐ray diffraction and molecular modeling, the atomic‐level crystal structures of eight typical conjugated polymers are built. These eight crystal structures compose a crystal structure database of conjugated polymers, covering widely used molecular segments in organic optoelectronics. The crystal structure database can be used to predict the packing structures and charge transport of other related polymers.